The current status of tumor microenvironment and cancer stem cells in sorafenib resistance of hepatocellular carcinoma - Chen, Siqi; Du, Yaqing; Guan, Xin-Yuan; Yan, Qian (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is a heterogeneous and aggressive liver cancer that presents limited treatment options. Despite being the standard therapy for advanced HCC, sorafenib frequently encounters resistance, emphasizing the need to uncover the underlying mechanisms and develop effective treatments. This comprehensive review highlights the crucial interplay between the tumor microenvironment, cancer stem cells (CSCs), and epithelial-mesenchymal transition (EMT) in the context of sorafenib resistance. The tumor microenvironment, encompassing hypoxia, immune cells, stromal cells, and exosomes, exerts a significant impact on HCC progression and therapy response. Hypoxic conditions and immune cell infiltration create an immunosuppressive milieu, shielding tumor cells from immune surveillance and hindering therapeutic efficacy. Additionally, the presence of CSCs emerges as a prominent contributor to sorafenib resistance, with CD133+ CSCs implicated in drug resistance and tumor initiation. Moreover, CSCs undergo EMT, a process intimately linked to tumor progression, CSC activation, and further promotion of sorafenib resistance, metastasis, and tumor-initiating capacity. Elucidating the correlation between the tumor microenvironment, CSCs, and sorafenib resistance holds paramount importance in the quest to develop reliable biomarkers capable of predicting therapeutic response. Novel therapeutic strategies must consider the influence of the tumor microenvironment and CSC activation to effectively overcome sorafenib resistance in HCC.